Relato de caso e estudo da evolução de desempenho em provas objetivas de uma "Turma Olímpica" - Dantas, José Rodolfo Figueiredo (2024)
This work is a case report of a course conducted between the months of July and December 2023 in the municipality of Cabedelo-PB. Students in the 6th and 7th grades (level 1) of the municipal education system of this city, interested in acquiring more mathematics content in addition to the regular classes of the school year, participated in a preparatory course for mathematics competitions such as OBMEP, Cactus Olympiad, among others. In this way, the so-called "Olympic Class"was guided by material prepared by the Cactus Association Company in partnership with the Department of Education of the municipality of Cabedelo-PB, and the course was taught to the students both in person and virtually. During the program, objective evaluations were carried out with the aim of observing the progress of the class throughout the process and the advantages arising from this proposal.